Supplier Collaboration and Performance of Food and Beverage Manufacturing Firms in Kenya - Mulweye, David; Shale, Noor; Namusonge, Eric; Wachiuri, Elizabeth (International Journal of Supply Chain Management, 2024)
Purpose: This study sought to evaluate explored the influence of supplier collaboration on the performance of food and beverage manufacturing firms in Kenya and to find out the moderating effect of supply chain technology on the performance of food and beverage manufacturing firms in Kenya. Methodology: The study used exploratory research design and utilized both qualitative and quantitative data in carrying out the study. This study adopted a census survey sampling which was conducted on 270 food and beverage manufacturing firms in Kenya registered by Kenya Association of Manufacturers (KAM, 2022). The target population for the research was all 270 respondents each from the food and beverage manufacturing firms. Both primary and secondary data was used, the primary data was collected using semi structured questionnaire that was administered by the researcher and research assistants. Samples of the questionnaire were pilot tested to test the reliability and validity before full scale data collection. The data was analyzed using the Statistical Package for Social Sciences (SPSS) version 26 software. Quantitative data was analyzed using descriptive statistics and presented in tables and figures. The inferential analysis was further carried out using structural equation modelling, ANOVA and regression coefficients. The results were then presented using tables, figures, graphs and charts. Findings: Supplier collaboration significantly influenced performance of food and beverage manufacturing firms in Kenya at both without a moderator and also using the moderating variable, supply chain technology. In the first model without moderator, it recorded a standardized estimate of 0.637 (p<0.001), indicating that as supplier collaboration increases performance of food and beverage manufacturing firms also increases. Fit indices on structural equation modelling revealed a marginal fit with a chi-square test of 216.155 with 86 degrees (P-value 0.0561). The structural path for structural equation modelling from supplier collaboration to supply chain performance remains positive and significant standardized estimate of 0.855 and p-value was 0.001<0.05. Which indicates that the variability of supplier collaboration on the performance of food and beverage manufacturing firms could be explained by 63.7% when no moderator is included and increase to 85.5% when supply chain technology is incorporated thereby indicating a stronger relationship. The other fit indices that gave a satisfactory model fit are RMR=.9019, GFI= .9774, NFI= .9164, RMSEA=.0191 and CFI=.9176 this implies that the model was fit to determine the relationship between supplier collaboration and performance of food and beverage manufacturing firms in Kenya and therein make conclusions and recommendations. ANOVA, regression coefficient ant model summary (R2) were also used and indicated significance of there use all recording p-value of 0.000<0.05. Unique Contribution to Theory, Practice and Policy: While transaction cost theory used in this study was validated by offering cost reduction strategies like outsourcing, accurate order forecasting as increasing the organization bottom line. The study recommends that when creating a supplier collaboration portfolio, companies should pool suppliers with the same activities in one pool but to use technology to mop up suppliers with high asset specificity for components delivering competitive advantage. Meanwhile, suppliers with low asset specificity for suppliers with components which result to less competitive advantage needs to be managed as a separate line of engagement.